DETERMINAN DANA PIHAK KETIGA DAN HUBUNGANNYA TERHADAP KREDIT BANK UMUM (STUDI KASUS PROVINSI JAMBI) - Andri Devita (Universitas Batanghari Jambi, 2018)
This study uses secondary data collected by research object in Jambi Province in the form of data of third party fund of commercial banks, interest rate and total credit data and economic growth sourced from Bank Indonesia as well as and Central Bureau of Statistics (BPS). Data were collected during the period 2004 to 2015. Objectives of the study 1). analyze the factors that influence the Third Party Fund (DPK) of Jambi Province. 2). analyzing the relationship of third party funds (DPK) to the amount of credit disbursed by commercial banks in Jambi Province. The analytical tool used is focusing on multiple linear regression analysis in time series and correlation person through with the help of software SPSS series 21.0. Based on the discussion of data analysis results in this study, can be drawn conclusion as follows: 1). bank interest rate variable negatively and insignificant to third party funds Jambi Province, while the number of banks and economic growth significantly influence third party funds Jambi Province during the period 2004-2015 with R-square 99.3%. 2). the relationship between third party funds and bank credit distribution is very strong with correlation value of 0.994 x 100% = 99.40%.Keywords: Bank Interest Rate, Third Party Funds, Economic Growth, and Bank Loans